Fluorometric detection of fluoride and thiocyanate ions using novel anthrapyrazolone derivatives. (2021) - Saravanan, S.; Sheeba Rani, Thirupathy Mathew; Deepak Nazare, Aishwarya; Nutalapati, Venkatramaiah; Maji, Samarendra
Abstract: Anion recognition and sensing via artificial receptors have attracted a great deal of attention due to their significant role in chemical, biological, medical, and environmental applications. In the present investigation, we have demonstrated facile and straightforward synthesis of three low molecular weight fluorophore molecules designated as 2, 7 - dihydrobenzo [1, 2, 3 - cd:4, 5, 6-c'd']bis(indazole) [DHBBI], 2-(benzo[1, 2, 3-cd:4, 5, 6-c'd']bis(indazole)-2(7H)-yl)ethanol [DHBBI-OH] and 2-(benzo[1, 2, 3-cd:4, 5, 6-c'd']bis(indazole)-2(7H)-yl)ethyl methacrylate [DHBBI-MA] for the fluorometric detection of fluoride and thiocyanate ions in solution phase. DHBBI was synthesized by a condensation reaction of 1, 5-dichloroanthraquinone with hydrazine monohydrate. DHBBI-OH was synthesized by the reaction of DHBBI with 2-bromoethanol using K2 CO3 as base whereas, DHBBI-MA was synthesized by the reaction of DHBBI-OH with methacrylic anhydride using dimethylamino pyridine (DMAP). Novel three molecules were characterized by 1 H NMR, FT-IR, HR-MS and UV–Vis spectroscopy. The strong fluorescence nature of the compounds was further analyzed towards the detection of different ions. All the compounds DHBBI, DHBBI-OH, and DHBBI-MA showed turn on fluorescence behavior for fluoride (F - ) ion and turn off fluorescence behavior for thiocyanate (SCN - ) ion respectively.